2019
DOI: 10.1130/b35074.1
|View full text |Cite
|
Sign up to set email alerts
|

The duration and magnitude of Cretaceous cool events: Evidence from the northern high latitudes

Abstract: The Early Cretaceous (145–100 Ma) was characterized by long-term greenhouse climates, with a reduced equatorial to polar temperature gradient, although an increasingly large body of evidence suggests that this period was punctuated by episodic global “cold snaps.” Understanding climate dynamics during this high-atmospheric CO2 period of Earth’s history may have significant impact on how we understand climatic feedbacks and predict future global climate changes under an anthropogenically-driven high-pCO2 atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 87 publications
2
51
0
Order By: Relevance
“…A similar shift from terrestrial to marine conditions has been reported from early Aptian strata on High Arctic Svalbard, where inner shelf deposits of the Carolinefjellet Formation replaced fluvial and marginal marine sandstone of the Helvetiafjellet Formation ( Fig. 8B; Midtkandal et al, 2016;Vickers et al, 2016Vickers et al, , 2019. Chemostratigraphy places this transition into the negative carbon isotope excursion at the onset of OAE 1a (Midtkandal et al, 2016;Vickers et al, 2016Vickers et al, , 2019, indicating a similar age for the basinal Carolinefjellet Formation and the Rondon Member at Glacier Fiord (Fig.…”
Section: Potential Drivers Of Sea-level Change In the Sverdrup Basinsupporting
confidence: 75%
See 1 more Smart Citation
“…A similar shift from terrestrial to marine conditions has been reported from early Aptian strata on High Arctic Svalbard, where inner shelf deposits of the Carolinefjellet Formation replaced fluvial and marginal marine sandstone of the Helvetiafjellet Formation ( Fig. 8B; Midtkandal et al, 2016;Vickers et al, 2016Vickers et al, , 2019. Chemostratigraphy places this transition into the negative carbon isotope excursion at the onset of OAE 1a (Midtkandal et al, 2016;Vickers et al, 2016Vickers et al, , 2019, indicating a similar age for the basinal Carolinefjellet Formation and the Rondon Member at Glacier Fiord (Fig.…”
Section: Potential Drivers Of Sea-level Change In the Sverdrup Basinsupporting
confidence: 75%
“…To date, most research on OAE 1a has focused on sedimentary archives from low and mid-latitudes, while studies from high-latitude environments are scarce due to their remoteness (Herrle et al, 2015;Midtkandal et al, 2016;Vickers et al, 2016Vickers et al, , 2019. Recent studies of outcrops on Axel Heiberg Island (Nunavut, Canada; Fig.…”
Section: ■ Introductionmentioning
confidence: 99%
“…interval (potentially associated with the "cold snap"; Mutterlose et al, 2009) may reflect on a shift in climate and Hadley cell circulation, driven by a decrease in atmospheric pCO2 (e.g., Hasegawa et al, 2012). Indeed, other sedimentological evidence (e.g., glendonites) provide further support for relatively cold conditions at high northern latitudes associated with this interval (Vickers et al, 2019). For our records,, atmospheric pCO2 drops during the C10 interval from pre-and post-segment values within error of 1000 ppmv, to < 350 ppmv in the C10 interval ( Fig.…”
Section: Aptian-albian Variations In Atmospheric Pco2 Climate and Thmentioning
confidence: 94%
“…Multiple climate events (including OAEs) have been identified during the late Early Cretaceous (Vickers et al, 2019;Jenkyns, 2018) oftentimes referred to as the mid-Cretaceous (i.e., here, our records span the Aptian-Albian; 125 to 100.5 Ma). While limited, available temperature records (e.g., Jenkyns, 2018) and high latitude sedimentological evidence (Vickers et al, 2019) suggest a relatively cool interval (following warmth during OAE 1a) associated with a global carbon isotope maximum (i.e., "C10"; Bralower et al, 1999;Menegatti et al, 1998;Mutterlose et al, 2009) at the Aptian-Albian boundary prior to OAE 1b (Bottini et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation